Ambient particulate air pollution and blood pressure in peri-urban India - Curto, Ariadna (Epidemiology, 2019)
BACKGROUND: Evidence linking long-term exposure to particulate air pollution to blood pressure (BP) in high-income countries may not be transportable to low- and middle-income countries. We examined cross-sectional associations between ambient fine particulate matter (PM(2.5)) and black carbon (BC) with BP (systolic [SBP] and diastolic [DBP]) and prevalent hypertension in adults from 28 peri-urban villages near Hyderabad, India. METHODS: We studied 5531 participants from the Andhra Pradesh Children and Parents Study (18-84 years, 54% men). We measured BP (2010-2012) in the right arm and defined hypertension as SBP ≥130 mm Hg and/or DBP ≥80 mm Hg. We used land-use regression models to estimate annual average PM(2.5) and BC at participant’s residence. We applied linear and logistic nested mixed-effect models stratified by sex and adjusted by cooking fuel type to estimate associations between within-village PM(2.5) or BC and health. RESULTS: Mean (SD) PM(2.5) was 33 μg/m(3) (2.7) and BC was 2.5 μg/m(3) (0.23). In women, a 1 μg/m(3) increase in PM(2.5) was associated with 1.4 mm Hg higher SBP (95%CI: 0.12, 2.7), 0.87 mm Hg higher DBP (95%CI: -0.18, 1.9) and 4% higher odds of hypertension (95%CI: 0%, 9%). In men, associations with SBP (0.52 mm Hg; 95%CI: -0.82, 1.8), DBP (0.41 mm Hg; 95%CI: -0.69, 1.5), and hypertension (2% higher odds; 95%CI:-2%, 6%) were weaker. No associations were observed with BC. CONCLUSIONS: We observed a positive association between ambient PM(2.5) and BP and hypertension in women. Longitudinal studies in this region are needed to corroborate our findings.